Healthy Living Patterns Towards Diabetes Mellitus: A Literature Review - Ni Wayan Trisnadewi; Agus Supinganto (Universitas STRADA Indonesia, 2022)
Health problems that occur due to an unhealthy lifestyle are chronic diabetes mellitus type 2. Prevention of this disease needs to be done by improving lifestyle. This literature review is to describe lifestyle patterns associated with the incidence of type 2 diabetes mellitus. Database search used ProQuest, Science Direct, Pubmed, Cochrane Library, EBSCOhost, Sage Publications. The search keywords for articles were typed 2 diabetes, healthy lifestyle, healthy behavior, healthy living habits, healthy eating patterns, healthy activities, 31 articles were found and only 15 articles matched the analysis of objectives, suitability of topics, research methods used, sample size, ethics research, the results of each article, and the limitations. Results: The results showed that a healthy life was designed by habits in the family and the environment. Action against degenerative diseases that commonly occur in diabetes can be done by providing interventions to individuals, families, groups, and communities.